TINJAUAN SUMBER DAYA MANUSIA BAGIAN PENDAFTARAN RAWAT JALAN GUNA MENUNJANG PELAYANAN PRIMA DI RSUD CIKALONGWETAN - Harto, Suharto Harto; Auliadina, Laili Sania Hurin (Jurnal TEDC; Vol 18 No 3 (2024): JURNAL TEDCDO - 10.70428/tedc.v18i3.877, 2024)
Based on the preliminary study conducted by the author in February 2024 at RSUD Cikalongwetan, the registration system is still transitioning to electronic medical records. The registration queue is still manual, there are 4 outpatient registration counters, and all outpatient registration staff lack a medical record background. This research aims to review the Human Resources of the Outpatient Registration Department to support excellent service at RSUD Cikalongwetan. The research method used is descriptive with a qualitative approach. The subjects of this study are the 4 outpatient registration staff, while the object of the research is the outpatient registration section at RSUD Cikalongwetan. Data collection techniques include interviews, observations, documentation studies, and literature reviews. Research instruments used are writing tools, a stopwatch, a recording device, a camera, interview guidelines, and a checklist. The results show that the Standard Operating Procedure (SPO) for outpatient registration at RSUD Cikalongwetan meets the standards of PERMENKES No.24 of 2022 regarding Medical Records. However, the classification of Human Resources in the outpatient registration department does not meet the standards of KMK No.312 of 2020, PERMENKES No.55 of 2013, and Law No.17 of 2023. The staff's abilities, attitudes, appearance, attention, and actions are in line with the standards of excellent service, but the responsibility indicators do not meet these standards. The hospital has not yet implemented a regular training program for outpatient registration staff to support excellent service. The author suggests that the hospital should update its human resources, ensure staff are more meticulous, conduct monitoring and evaluation, ensure staff punctuality, and provide regular training for outpatient registration staff.